The mediating effect of organizational commitment on the relationship between HRM practices and intention to leave - Nurellman, Ismail (2014)
The year of 2020 has come near and Malaysia is in need of highly committed, competitive, productivity and efficient work forces to fulfil its Vision 2020 program. The purpose of this study was to examine the impact of HRM practices toward intention to leave and to investigate the influence of organization commitment as a mediator in the relationship between HRM practices and intention to leave among lecturers in various public universities in northern Malaysia. Internet survey questionnaires were sent using e – mail to 221 respondents working as lecturers in the public universities. Statistical Package software for Social Science (SPSS) Version 19.0 to analyze the data gathered. Pearson’s Correlation analysis was done to examine the relationship between all variable and was found that all HRM practices and organizational commitment have significant negative relationship with intention to leave. Multiple regressions analysis was conducted to test the hypotheses. It was found that not only HRM practices decrease employee’s intention to leave, the results also show that this relationship was partially mediated by organizational commitment. It is also suggested for the future research to include some other HRM practices that was not include in this study to examine its influence toward intention to leave. It is also recommendable to examine these relationships in other settings outside of academic sector